Urinary 8-hydroxydeoxyguanosine levels and psychological reactions after sleep deprivation - Ikegami, Kazunori; Ogyu, Seizo; Arakomo, Yuko; Shirakawa, Chie; Suzuki, Kiyomi; Tahara, Hiroyuki; Moriyama, Koji; Mafune, Kosuke; Hiro, Hisanori; Nagata, Shoji; Kasai, Hiroshi (Journal of UOEH, 2010)
The aim of this study was to investigate whether changes in urinary 8-hydroxydeoxyguanosine (8-OH-dG), an oxidative stress indicator, occur or not, and how psychological reactions change, after one night of sleep deprivation (SD) and after 7 hour recovery sleep opportunities during three recovery days. Twenty healthy subjects participated in this study. We measured their urinary 8-OH-dG levels and psychological reactions using the Profile of Mood States (POMS) for 5 days: on the baseline day, the post-vigil day, and on 3 recovery days after SD. The urinary 8-OH-dG levels and subscale scores of POMS were analyzed using repeated analysis of variance (ANOVA). In the psychological reactions, the values of Vigor on the post-vigil day and 2nd recovery day were significantly lower than on the baseline day. Fatigue and confusion on the post-vigil day were significantly higher than on the baseline day, and on the 1st and 2nd recovery days were relatively higher compared to the baseline day but returned to baseline level on the 3rd recovery day. The urinary 8-OH-dG levels did not change significantly after SD, on the post-vigil day or on the 3rd recovery days. These results suggest that the effect of one night of SD on psychological reactions continued for 2 or 3 days, and SD might not influence urinary 8-OH-dG levels despite marked changes in psychological reactions.